Solubilization of caffeic acid into the cationic micelles and biogenic synthesis of silver nanoparticles for the degradation of dye - Zoya Zaheer (Journal of Saudi Chemical Society, 2022)
Solubilization of caffeic acid into the aqueous solution of cationic cetyltrimethlyammonium bromide (CTAB) has been studied by using differential spectroscopic and conductivity methods. The solubility of caffeic acid increases with increasing the CTAB concentrations. The solubilization constant of caffeic acid into CTAB (KX = 1.8 × 105), standard free energy (ΔG0P = −30.0 kJ/mol), and relative solubility (St/S0 = 53.5) were estimated at room temperature from UV–visible data. The critical micellar concentration (CMC) of CTAB decreases linearly with caffeic acid concentration due to the presence of hydrophobic benzene moiety. The interaction of caffeic acid with CTAB has also been discussed. The solubilized caffeic acid was used as a reducing agent for the preparation of silver nanoparticles (AgNPs). The as-prepared AgNPs were used as an activator of persulphate. The generated reactive oxygen species (OH•) and reactive sulphur species SO4-•) were responsible for the degradation of xylenol orange dye in water.